Gestational Diabetes Mellitus and Metabolic Disorder Among the Different Phenotypes of Polycystic Ovary Syndrome - Mahnaz Ashrafi; Fatemeh Sheikhan; Arezoo Arabipoor; Nicole Rouhana; Roya Hosseini; Zahra Zolfaghari (Oman Medical Journal, 2017)
Objectives: Polycystic ovary syndrome (PCOS) is a common endocrine disorder related to several metabolic consequences. However, there remains uncertainty regarding the metabolic features of various phenotypes. The aim of this study was to explore the relationship between the prevalence of gestational diabetes mellitus (GDM) and metabolic disorders among the four different phenotypes of PCOS. Methods: A cross-sectional study was performed in Royan Institute including 208 pregnant women with a history of infertility and PCOS. Using the diagnostic criteria of the American Diabetes Association (ADA), pregnant women with a documented diagnoses of PCOS were further categorized into four different phenotypes (A, B, C, and D) as defined by the Rotterdam criteria. Results: The prevalence of GDM failed to demonstrate a significant relationship among the four phenotypes of PCOS. The mean levels of fasting blood sugar, plasma glucose concentrations at three hours (following the 100 g oral glucose tolerance test) and triglyceride levels were significantly higher in phenotype B compared to the remaining phenotypes (p < 0.050). There was a statistically significant difference between the mean free testosterone level and phenotypes A and C groups (1.8±1.6 vs. 1.1±1.0, p = 0.003). Conclusions: Women with a known diagnosis of PCOS who exhibited oligo/anovulation and hyperandrogenism demonstrated an increase of metabolic disorders. These results suggest that metabolic screening, before conception or in the early stages of pregnancy, can be beneficial particularly in women with PCOS phenotypes A and B. Early screening and identification may justify enhanced maternal fetal surveillance to improve maternal and fetal morbidity among women affected with PCOS.